Identity‐based motivations and anticipated reckoning: Contributions to gift‐giving theory from an identity‐stripping context1. Issue 3 (15th January 2015) - Klein, Jill G.; Lowrey, Tina M.; Otnes, Cele C.
Abstract: We utilize the Identity‐Based Motivation (IBM) model to examine gift giving within the identity‐stripping context of Nazi concentration camps, as reported in the memoirs of Holocaust survivors. By exploring gift giving in this crisis‐laden context, we demonstrate the fundamental role gifts can play in reestablishing personal and social identities. In doing so, we provide insights into the motivations for giving that go beyond the existing paradigms that emphasize social exchange, economic exchange, or agapic giving. Further, we introduce the construct of anticipated reckoning, in which people self‐regulate their behavior through an imagined future self whom they perceive to judge their current actions.